2022
DOI: 10.14393/bj-v38n0a2022-62653
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic parameters of captive Bothrops atrox (Squamata: viperidae)

Abstract: The breeding of venomous snakes in captivity for research purposes and mainly as a source of pharmaceutical products highlights the need to determine hematological parameters for monitoring and ensuring a healthy breeding populationThe complete blood count is used to help diagnose alterations such as anemia, inflammatory diseases, parasitemia, hematopoietic disorders, hemostatic and toxicological changes, as well as bacterial and viral inclusions. Thus, the objective of this study was to define reference param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…In general, most of the hematological parameters do not differ significantly from those of other tropical vipers, and the leukocyte distribution is similar to that of Crotalus durissus , B. leucurus , Bothrops jararaca , and Bothoriopoides jararacussu , where lymphocytes are the most prevalent cell population, followed by azurophils. However, for example, Bothrops ammodytes have lymphocytes as the first cell but eosinophils and then heterophils as the second and third cells, leaving the azurophil as the fourth cell population, which is different from what Pereira et al (2022) found for Bothrops atrox , where heterophils were the first line, followed by lymphocytes. Although Lachesis is a genus confined to tropical areas, it is more closely related phylogenetically to the genera Ophryacus (a genus endemic to Mexico) and Agkistrodon ( Castoe and Parkinson, 2006 ; Alencar et al ., 2016 ; Pyron, 2017 ); therefore, it is probably more accurate to compare its parameters with those of copperheads.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…In general, most of the hematological parameters do not differ significantly from those of other tropical vipers, and the leukocyte distribution is similar to that of Crotalus durissus , B. leucurus , Bothrops jararaca , and Bothoriopoides jararacussu , where lymphocytes are the most prevalent cell population, followed by azurophils. However, for example, Bothrops ammodytes have lymphocytes as the first cell but eosinophils and then heterophils as the second and third cells, leaving the azurophil as the fourth cell population, which is different from what Pereira et al (2022) found for Bothrops atrox , where heterophils were the first line, followed by lymphocytes. Although Lachesis is a genus confined to tropical areas, it is more closely related phylogenetically to the genera Ophryacus (a genus endemic to Mexico) and Agkistrodon ( Castoe and Parkinson, 2006 ; Alencar et al ., 2016 ; Pyron, 2017 ); therefore, it is probably more accurate to compare its parameters with those of copperheads.…”
Section: Discussioncontrasting
confidence: 66%
“…Most of the information on hematology and blood biochemistry in neotropical vipers comes from studies carried out in Brazil, Argentina, Peru, and Costa Rica ( Troiano et al , 1997 , 1999 , 2000 , 2001 ; Grego et al , 2006 ; Rameh-de-Albuquerque et al , 2007 ; Silva et al , 2010 ; Ghilardi and Zacariotti, 2013 ; Glaser et al , 2013 ; Gómez et al ., 2016 ; Trujillo et al ., 2016 ; Pereira et al , 2022 ). These investigations were made for the genera Crotalus , Bothrops , Bothropoides, and Caudisona , obtaining ranges of values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation